2015
DOI: 10.1111/1747-0080.12167
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural factors and perceptions associated with type 2 diabetes among sub‐Saharan African migrants in Melbourne, Victoria

Abstract: Aim:To explore how non-diabetic sub-Saharan African migrants residing in Melbourne, construct and interpret type 2 diabetes mellitus (T2DM) and its risk factors and to provide an evidence-based theoretical framework to inform community-based prevention programs. Methods: Seven focus group discussions (two with women only, two with men only and three of mixed gender) were carried out among Ghanaian, Zimbabwean, Sudanese and Burundian migrants living in Melbourne (n = 61; age range: 18 to 61 years). Results: Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…This study revealed a diversity of beliefs among Nigerian immigrants about hypertension. Its findings show that although there may be many similarities across sub-Saharan African migrants’ beliefs and values about illnesses such as diabetes and hypertension [ 15 , 46 , 48 ], there may be subtle differences not previously identified in the literature. It is therefore important to explore beliefs of migrants from individual countries of origin and if possible specific in-country ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed a diversity of beliefs among Nigerian immigrants about hypertension. Its findings show that although there may be many similarities across sub-Saharan African migrants’ beliefs and values about illnesses such as diabetes and hypertension [ 15 , 46 , 48 ], there may be subtle differences not previously identified in the literature. It is therefore important to explore beliefs of migrants from individual countries of origin and if possible specific in-country ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other studies which investigated the beliefs about hypertension among ethnic minority groups in the United Kingdom [ 15 , 20 – 27 , 46 ] and other developed nations [ 37 , 43 , 47 ]. There have also been studies which investigated the beliefs regarding other chronic health conditions among immigrant communities in developed countries [ 48 , 49 ]. However this is the first study that has explored the beliefs, perceptions and attitudes regarding hypertension among Nigerians living in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Still, countries hosting immigrants are facing challenges in diabetes prevention among highly diverse immigrant communities [ 7 ]. This challenge partially stems from the fact that many immigrant communities have different concepts of health and health care than mainstream societies in the host country [ 14 ]. Therefore, to meet immigrant's preventive health needs, hosting countries need a greater understanding of the health status, health behaviors, and risk factors prevalent in different groups within the population.…”
Section: Introductionmentioning
confidence: 99%
“…The language proficiency is another factor that affects immigrants' exposure to preventive services, with immigrants who do not speak the national language being less likely to benefit from community-based health promotion programs. Immigrants from sub-Saharan Africa were reported to not pay much attention to T2D, considering it something beyond an individual's control [ 14 ]. Therefore, due to misconceptions indicated by popular health beliefs, many Africans fail to take appropriate measures for the prevention and control of diabetes and its risk factors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop culturally appropriate programs to increase health and nutrition literacy, and thereby improve food and nutrition security among migrant groups, insights into perceptions about their health‐seeking behaviours are required. A qualitative study of sub‐Saharan African migrants residing in Melbourne identified three distinct themes with regard to perceptions related to diabetes . Participants did not pay much attention to the threat of type 2 diabetes, considered the disease to be outside of their control and being a disease associated with culture and life style of rich industrialised countries.…”
Section: A New Paradigm To Address Food Insecuritymentioning
confidence: 99%